The E3 ligase Cbl-b and TAM receptors regulate cancer metastasis via natural killer cells - Paolino, Magdalena (2014)
Tumour metastasis is the primary cause of mortality in cancer patients and remains the key challenge for cancer therapy. New therapeutic approaches to block inhibitory pathways of the immune system have renewed hopes for the utility of such therapies2. Here we show that genetic deletion of the E3 ubiquitin ligase Cbl-b (casitas B-lineage lymphoma-b) or targeted inactivation of its E3 ligase activity licenses natural killer (NK) cells to spontaneously reject metastatic tumours. The TAM tyrosine kinase receptors Tyro3, Axl and Mer (also known as Mertk) were identified as ubiquitylation substrates for Cbl-b. Treatment of wild-type NK cells with a newly developed small molecule TAM kinase inhibitor conferred therapeutic potential, efficiently enhancing anti-metastatic NK cell activity in vivo. Oral or intraperitoneal administration using this TAM inhibitor markedly reduced murine mammary cancer and melanoma metastases dependent on NK cells. We further report that the anticoagulant warfarin exerts anti-metastatic activity in mice via Cbl-b/TAM receptors in NK cells, providing a molecular explanation for a 50-year-old puzzle in cancer biology3. This novel TAM/Cbl-b inhibitory pathway shows that it might be possible to develop a a 'pill' that awakens the innate immune system to kill cancer metastases. © 2014 Macmillan Publishers Limited.